A geometria euclidiana na licenciatura em matemática do ponto de vista de professores formadores - Ramassotti, Luiz Carlos [UNESP] (2015)
This research presents the view of a group of lecturers of undergraduate courses on how Euclidian Geometry should be approached in a Mathematics Degree Program, so that the graduating teacher has knowledge of geometry adequate for work on Middle and High School Education. The data collection method was questionnaire and interview, in which it is tried to identify the interviewee take on: rigor level of how axiomatization and formalization of geometry are presented, teaching strategies and how important the use of a ruler and compass is to the undergraduate formation of teachers. Taking into consideration modern technologies, it was also intended to highlight their opinions on the introduction to dynamic geometry softwares in Undergraduate Mathematics Education, specifically for the study of Geometry. The research sought to identify geometry textbooks that they consider adequate for the instruction of math teachers and pinpoint the reasons why there has been a neglect of geometry in Middle and High School classrooms. The interviewees shows that Euclidian Geometry must be presented in a strict axiomatic and formal way. In one demonstration the figure is an important teaching aid, being the demonstration justified by results and theorems already proven. Because of students lack of ability to comprehend the formal axiomatic system, it is suggested that geometry be studied closer to the end of courses to provide better understanding and knowledge retention. Ruler and Compass are found to be essential. Combined with important use of dynamic geometry sotware, these teachings aids will improve visualization and movement. The existing Brazilian Bibliography must be supplemented by foreign works, concluding that there is a need of reference works in this área in our country. The lack of specific knowledge and teaching tools is pointed as the reason for the absence of geometry in the Middle and High School classroom, problem originated in the ...